A NEW SPECIES OF DICHAEA (ORCHIDACEAE: ZYGOPETALINAE) FROM THE ANDES OF COLOMBIA - Alomía, Yasmin A.; Sambin, Aurelien; Otero, J. Tupac; Stevenson, Pablo R. (Phytotaxa, 2021)
A new species of Dichaea sect. Dichaea from the Andean forests in Colombia is described and illustrated based on living material. Dichaea andina is compared with the morphologically similar D. lagotis and D. pendula, from which it can be distinguished by a number of vegetative and floral and features. Dichaea andina differs from D. lagotis in the broadly anchoriform lip, the hypochile transversely subrounded and the epichile transversely narrowly elliptic, briefly apiculate. Similarly, it differs from D. pendula in the caespitose habit, the leaves without cross-venation, and the inflorescence straight produced below the foliage, among other features. Ecological information for the new species is also provided.